Sovereign debt ratings and stock liquidity around the World - Lee, Kuan-Hui; Sapriza, Horacio; Wu, Yangru (Journal of Banking & Finance, 2016)
This paper studies the impact of sovereign debt rating changes on liquidity for stocks from 40 countries for the period 1990–2009. We find that sovereign rating changes significantly affect stock liquidity. The impact is stronger for downgrades than for upgrades, and is nonlinear in event size. The loss of investment grade has a particularly strong negative impact on stock liquidity. We also find that some stock characteristics and country legal and macroeconomic environment are important in explaining the differences in the impact of sovereign credit rating changes on stock liquidity across countries.